Methanol and ethanol modulate responses to danger- and microbe-associated molecular patterns - Hann, Claire T.; Bequette, Carlton J.; Dombrowski, James E.; Stratmann, Johannes W. (Frontiers in Plant Science, 2014)
Methanol is a byproduct of cell wall modification, released through the action of pectin methylesterases (PMEs), which demethylesterify cell wall pectins. Plant PMEs play not only a role in developmental processes but also in responses to herbivory and infection by fungal or bacterial pathogens. Molecular mechanisms that explain how methanol affects plant defenses are poorly understood. Here we show that exogenously supplied methanol alone has weak effects on defense signaling in three dicot species, however it profoundly alters signaling responses to danger- and microbe-associated molecular patterns (DAMPs, MAMPs) such as the alarm hormone systemin, the bacterial flagellum-derived flg22 peptide, and the fungal cell wall-derived oligosaccharide chitosan. In the presence of methanol the kinetics and amplitudes of DAMP/MAMP-induced MAP kinase (MAPK) activity and oxidative burst are altered in tobacco and tomato suspension-cultured cells, in Arabidopsis seedlings and tomato leaf tissue. As a possible consequence of altered DAMP/MAMP signaling, methanol suppressed the expression of the defense genes PR-1 and PI-1 in tomato. In cell cultures of the grass tall fescue (Festuca arundinacea, Poaceae, Monocots), methanol alone activates MAPKs and increases chitosan-induced MAPK activity, and in the darnel grass Lolium temulentum (Poaceae), it alters wound-induced MAPK signaling. We propose that methanol can be recognized by plants as a sign of the damaged self. In dicots, methanol functions as a DAMP-like alarm signal with little elicitor activity on its own, whereas it appears to function as an elicitor-active DAMP in monocot grasses. Ethanol had been implicated in plant stress responses, although the source of ethanol in plants is not well established. We found that it has a similar effect as methanol on responses to MAMPs and DAMPs.